Exploring the English reading habits among teenagers / Azrina Abu Bakar - Abu Bakar, Azrina (2019)
Reading is part of literacy. Despite boasting a high Malaysia’s literacy rate, educationists and social analysts lament that the reading habits among Malaysians has dwindled with the prevalence of digital devices. The issue that this study addresses is the lack of teenagers in English reading. To address this problem, the purpose of this study was to investigate the English reading habits of English as a Second Language (ESL) students at Universiti Teknologi MARA (UiTM) Melaka, Malaysia in order to gain insights on their English reading culture. This study also examined the influences of school or university culture and family culture on students’ reading habits. To gather data, 100 students were selected randomly to complete a questionnaire. The data were analysed using the Statistical Package for Social Science (SPSS) Statistics 17.0 software. Furthermore, interviews with four students were conducted. The interviews were transcribed and analysed. From the statistical data, it was revealed that the students’ reading habits is still considered quite low. The researcher also found that family culture impacts the students’ reading habit. Some recommendations were made to educators, the librarians, and parents to nurture the students’ English reading habits.